Bridging the Gap: The Role of Nurses in Oral Health Promotion and Preventive Dental Care - AL NASS, ESRAA ZAKI; AL SHEEF, NOOR MUNEER; AL ZAHER, SAMIHA JAFFAR; ALMUTAWA, EMAN MAHDI; ALSHWAKAT, AMAL ALI; ALHARBI, THAMER ABDULLAH; ALSARHAN , RANA ABDULLAH; ALKHAYBRY, HIND AWAD EID; ALSHAQAQ, NIMAHALLAH JAWAD; ALMASHAYIKH , SHAHAD MOHAMMED AHMED; AL FATIL , ZAINAB ALI; AL TURAIK, MARYAM RADI; et al. (Journal of Posthumanism, 2024)
Oral health represents an essential yet often underestimated component of holistic human well-being. The oral cavity is not an isolated system; rather, it mirrors and influences systemic health. Oral health stands as a vital component of comprehensive well-being, demanding unified action from all healthcare sectors. The recognition of these associations emphasizes the need for healthcare systems to transcend disciplinary boundaries. For nurses and dentists alike, understanding these interrelationships fosters early detection, preventive interventions, and improved patient outcomes. The oral cavity, therefore, serves as both a diagnostic window and a therapeutic gateway for systemic disease management. The emergence of Artificial Intelligence (AI) in healthcare has transformed diagnostic and preventive paradigms across disciplines, including dentistry and nursing. Nurses and dentists can share datasets and protocols that advance standardized best practices globally. Global health organizations should promote equitable technology access, ensuring that low- and middle-income countries benefit from the same digital tools available in wealthier regions. Such collaborations embody the ethical imperative of using innovation to reduce—not reinforce—health disparities. Through education, innovation, and global cooperation, oral-systemic integration will become a defining feature of holistic, patient-centered healthcare worldwide.